Measuring the Benefits of Building Information Modeling (BIM) Adoption: Trends, Gaps, and Future Directions - Mohamed, Hanan-Allah; Mohamad Yusuwan, Norazian; Hashim, Norfashiha; Usman, Nuruddeen (International Journal of Sustainable Construction Engineering and Technology, 2023)
Building information modelling (BIM) adopters require well-documented, quantitative, and financial simulation studies as solid evidence for the benefits of BIM to implement it and evaluate its success. However, to move towards more practical analyses to be performed by the end-users, more discussions on process to measure BIM benefit should be held, despite the large number of studies related to BIM benefit indicators. Therefore, this study examines the proposed and simulated methods used to measure the benefits of BIM in previous studies. A systematic literature review (SLR) of 21 articles was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and analysed using meta-ethnography and thematic qualitative analysis. The SLR depicted the trends of studies published over the years. The results indicate that out of the 31 BIM benefits identified, only 17 BIM benefits have been measured in simulations. 4 other BIM benefits were suggested to be explored in line with their magnitude of importance. Comparative case studies were used conventionally to collect the data for measuring these benefits. This has since shifted to conducting case studies of single BIM projects along with supplementary data collection for counterfactual assessment. Furthermore, predictive ex-ante studies are currently blooming. At present, ongoing studies are being conducted to demonstrate the detailed technique with which to calculate and measure the benefits of BIM. This paper provides researchers and analysts with initial insights that can be used to move forward with BIM benefit measurements.